2021
DOI: 10.1371/journal.pone.0254708
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial distress amongst Canadian intensive care unit healthcare workers during the acceleration phase of the COVID-19 pandemic

Abstract: Intensive care unit healthcare workers (ICU HCW) are at risk of mental health issues during emerging disease outbreaks. A study of ICU HCW from France revealed symptoms of anxiety and depression in 50.4% and 30.4% of workers at the peak of the first wave of the pandemic. The level of COVID-19 exposure of these ICU HCW was very high. In Canada, ICU HCW experienced variable exposure to COVID-19 during the first wave of the pandemic, with some hospitals seeing large numbers of patients while others saw few or non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 21 publications
3
31
0
4
Order By: Relevance
“…The finding that women and nurses are at greater risk of psychological distress than men are is consistent across most studies. 6 , 15 , 24 , 25 , 27 , 28 , 30 33 This may reflect greater and more prolonged direct exposure of nurses than other HCPs to COVID-19 patients, which may be intensified by the disproportionate burden of family and domestic responsibilities shouldered by women. 34 …”
Section: Discussionmentioning
confidence: 99%
“…The finding that women and nurses are at greater risk of psychological distress than men are is consistent across most studies. 6 , 15 , 24 , 25 , 27 , 28 , 30 33 This may reflect greater and more prolonged direct exposure of nurses than other HCPs to COVID-19 patients, which may be intensified by the disproportionate burden of family and domestic responsibilities shouldered by women. 34 …”
Section: Discussionmentioning
confidence: 99%
“…This observation fits with the findings of Zhang et al, who found a higher prevalence of mental stress symptoms, such as anxiety and depression, in healthcare workers with direct contact to COVID-19-infected patients (N = 927) compared with nonmedical healthcare workers (N = 1255) [ 49 ]. A study on 310 Canadian HCWs also showed that the prevalence of psychosocial stress was highest among registered nurses (75.7%) and lowest among physicians (49.4%) [ 50 ]. Additionally, a systematic review by Busch et al also found that frontline staff were primarily concerned about infecting themselves (47%) or passing the virus to family members (60%) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rates of anxiety and depression were 14 and 19% in the general public in Hong Kong, respectively (Choi et al, 2020 ; Tang et al, 2020 ). For medical staff, a certain percentage of medical staff had anxiety, depression, burnout or clinically-relevant psychosocial distress, confirmed by investigation studies conducted in other countries such Kenya, Japan, and Canada (Binnie et al, 2021 ; Kwobah et al, 2021 ; Matsuo et al, 2021 ). In this study, the rates of anxiety and depression were 21.1 and 43.9% in the whole sample, respectively, which were lower than those in COVID-19 patients or the people with a special background and higher than those in other populations.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have also found that the occurrence of adverse psychological problems coexists with obvious gender and work position characteristics. For example, the occurrence rate of adverse psychological problems in nurses was higher than doctors, and the occurrence of adverse psychological problems in women was higher than men (Huang et al, 2020 ; Binnie et al, 2021 ; Kwobah et al, 2021 ). However, in this study, the rates of anxiety (20.7 vs. 21.2%) and depression (43.1 vs. 44.1%) in men and women were similar, and the rates of anxiety (21.3 vs. 21.0%) and depression (44.8 vs. 43.5%) in doctors and nurses were also similar.…”
Section: Discussionmentioning
confidence: 99%